2017
DOI: 10.1007/s10238-017-0473-2
|View full text |Cite
|
Sign up to set email alerts
|

Detection of promoter methylation status of suppressor of cytokine signaling 3 (SOCS3) in tissue and plasma from Chinese patients with different hepatic diseases

Abstract: SOCS3 as an important negative regulator of IL6/JAK/STAT3 signaling pathway may be early critical determinants of carcinogenesis. This study aimed to explore the aberrant promoter methylation of SOCS3 gene in circulating DNA as a noninvasive biomarker for screening hepatocellular carcinoma (HCC) high-risk individuals and for prognosis of HCC patients after partial hepatectomy. We detected its methylation status in 116 liver tissues and 326 plasma specimens of different hepatic diseases and healthy subjects, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 34 publications
0
24
0
1
Order By: Relevance
“…The model further differentiated patients with HCC from those with hepatitis B virus (HBV)/HCV infection and fatty liver disease [115]. Suppressor of cytokine signaling 3 (SOCS3) methylation in both HCC tissue and plasma was also found to be associated with tumor size and differentiation, metastasis, and recurrence, as well as with poorer prognosis [116].…”
Section: Cfdnamentioning
confidence: 99%
“…The model further differentiated patients with HCC from those with hepatitis B virus (HBV)/HCV infection and fatty liver disease [115]. Suppressor of cytokine signaling 3 (SOCS3) methylation in both HCC tissue and plasma was also found to be associated with tumor size and differentiation, metastasis, and recurrence, as well as with poorer prognosis [116].…”
Section: Cfdnamentioning
confidence: 99%
“…To investigate the methylation status of CpG islands of RASSF1A , p16 , SFRP1 , SOCS3 and LINE1, multiplex MSP was performed in a 25µL-volume reaction system, consisted of 50ng sodium-bisulfite treated DNA, isometric mixture of gene primers 3µL, 2×Master Mix 12.5µL (Qiagen, Germany) and ddH 2 O. The multiplex MSP primer sequences for RASSF1A , p16 , SFRP1 , SOCS3 and LINE1 were described in Table S1 11 , 14 , 20 - 22 . The reaction conditions were listed as follows: denaturation at 95℃ for 15 min, 30 cycles of 94℃ for 30s, annealing for 90s and 72℃ for 90s, with an ultimate extension of 10 min at 72℃.…”
Section: Methodsmentioning
confidence: 99%
“…Changes in DNA methylation have been shown to be pivotal in the development of HCC, particularly within the CpG islands of tumour suppressor genes. A number of studies have analysed methylation patterns in HCC tumour resections and reported hypermethylation of p15, CDKN2A (encoding for p16), glutathione S -transferase P1 ( GSTP1 ), Ras association domain family 1A ( RASSF1A ), APC, SOCS1, SOCS3, TIMP3, blood vessel epicardial substance (BVES) and Homeobox A9 (HOXA9) genes and hypomethylation of long interspersed element-1 (LINE-1) repetitive sequence within the tumours 6 29–35. However, the same methylation pattern was detectable in only a subproportion of the reported genes found in cfDNA/ctDNA; for example, hypermethylation of GSTP1 was detected in 50% of the cfDNA, RASSF1A was found in 70%–93% (depending on the study), whereas hypomethylation of LINE-1 was present in 66.7% of cfDNA in the sera of patients with HCC 32 33.…”
Section: Circulating Nucleic Acidsmentioning
confidence: 99%